2020
DOI: 10.21203/rs.3.rs-17055/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends of multimorbidity in 15 European countries: a population-based study in community-dwelling adults aged 50 and over

Abstract: Background: The objective of this work was to analyse the prevalence trends of multimorbidity among European community-dwelling adults.Methods: A temporal series study based on waves 1, 2, 4, 5, 6 and 7 of the Survey of Health, Ageing and Retirement in Europe (SHARE) was conducted, and community-dwelling participants aged 50+ (n=274,614) from 15 European countries were selected for the period 2004-2017. Prevalence, adjusted by age, Average Annual Percentage Change (APC) and 95% confidence interval (95% CI) we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Globally, approximately 37% of the general population has multimorbidity [15] and it is associated with premature death [16], poor health [17,18] depression [19], poor quality of life [20], and increased healthcare utilization [21]. Additionally, age, gender, educational level, smoking, and obesity were associated with multimorbidity in previous research among adults aged 50 and over [22]. Multimorbidity has become increasingly important as changing health behaviors, such as physical activity and obesity, are a core focus in multimorbidity prevention.…”
Section: Table Of Contentsmentioning
confidence: 99%
“…Globally, approximately 37% of the general population has multimorbidity [15] and it is associated with premature death [16], poor health [17,18] depression [19], poor quality of life [20], and increased healthcare utilization [21]. Additionally, age, gender, educational level, smoking, and obesity were associated with multimorbidity in previous research among adults aged 50 and over [22]. Multimorbidity has become increasingly important as changing health behaviors, such as physical activity and obesity, are a core focus in multimorbidity prevention.…”
Section: Table Of Contentsmentioning
confidence: 99%
“…See figure 2.1. However, the increase in men only was observed in Netherlands and the prevalence was relatively stable in other countries in the period under review (Souza et al, 2021). The increase or reduction in the prevalence of multimorbidity was explained by two factors: (1) changes in the prevalence of the main risk factors, such as tobacco and alcohol consumption, diet or practice of physical activity; or (2) changes in the classification system and/or improvement in diagnosis.…”
Section: Prevalence Of Multimorbidity In the Communitymentioning
confidence: 88%
“…Data from 15 European countries have shown that an increase in the prevalence of multimorbidity in both genders in 7 countries (Souza et al, 2021). See figure 2.1.…”
Section: Prevalence Of Multimorbidity In the Communitymentioning
confidence: 99%